Novel bicyclic pyrazoles as potent ALK2 (R206H) inhibitors for the treatment of fibrodysplasia ossificans progressiva. (15th April 2021) - Yamamoto, Hirofumi; Sakai, Naoki; Ohte, Satoshi; Sato, Tomohiro; Sekimata, Katsuhiko; Matsumoto, Takehisa; Nakamura, Kana; Watanabe, Hisami; Mishima-Tsumagari, Chiemi; Tanaka, Akiko; Hashizume, Yoshinobu; Honma, Teruki; et al.
Graphical abstract: Abstract: Mutant activin receptor-like kinase-2 (ALK2) is associated with the pathogenesis of fibrodysplasia ossificans progressiva, making it an attractive target for therapeutic intervention. We synthesized a new series of bicyclic pyrazoles and evaluated their mutant ALK2 enzyme inhibitory activities, leading to the identification of 8 as the most potent inhibitor. This compound showed moderate microsomal metabolic stability and human ether-a-go-go related gene (hERG) safety. In C2C12 cells carrying mutant ALK2 (R206H), 8 efficiently inhibited the bone morphogenetic protein (BMP)-induced alkaline phosphatase activity.